Logistic Growth And Density-Dependent Spatial And Temporal Invasion Predictions Of Non-Native Tilapia, Oreochomis Niloticus (Linnaeus 1757), In The Ganga River (India) (Applied Biological Research, 2020)
The changes in fishery yield owing to the exponential and logistic growth  of non-native tilapia Oreochomi niloticus, was studied and its concrete and  predictive invasion worked out so as to find out future level of invasion and  yield from the Ganga river, India. The results showed that the abundance  of O. niloticus ranged from 3.07 to 15.05% during 2009 to 2018 which  increased continually at eight studied locations. At the same time, the  average biomass yield day-1 also increased significantly (p < 0.05) in the  same period. The calculated mean abundance by weight (MAW) showed  that the average biomass was 51.95 kg day-1 km-1 during 2009 which  increased to 151 ± 3 kg day-1 km-1in 2018 showing 292% rise within a  decade. The biomass-dependent tilapia population revealed significant (p < 0.05) increase in exponential and logistic growth over the years even in the degraded water quality having higher BOD and COD. The predicted  increase in the mean abundance by weight-based biomass showed  significant change and the annual-regression was p < 0.419 considering the  incremental exponential and logistic growth. The predictive forecast of  invasive tilapia catches for the period of 2018 to 2028 at 95% confidence  limit suggests stable production from the Ganga river inviting attention of  scientists and managers towards its management.
Keywords: Abundance; growth; logistic biomass; prediction; tilapia